A comparative study on the effectivity of glass ionomer cement with the standard orthodontic bonding agent as a direct bonding material for orthodontic brackets - Garcia, Racquel M.
This study aims to evaluate the use of Glass Ionomer Cesnent as an alternative bonding agent for orthodontic brackets. The standard bonding material, composite resins offer more than adequate adhesive strength but it does not have the unique property of Glass ionomer Cement to chemically bond with tooth structure and the ability to release fluoride. A sample consisting of 50 recently extracted sound bicuspids was collected. The teeth were randomly divided into 5 groups of 10 and were bonded with Begg brackets using 4 different locally available Glass Ionomer Cements ( ChemfiL Chelon-fiL Fuji II, Variglass } and a standard orthodontic adhesive { OBAK ]. Each sample was tested using the Universal Instron Machine to determine the tensile strength.